Low profile printed antenna with a pair of steploading for dual-frequency operation - Ismail, M. K. H.; Esa, Mazlina (2003)
Several techniques have been reported to reduce the size of a microship antenna having dual operating frequencies. A single low profile printed antenna which pmvides dual-bad operation by having two-step slots loading embedded close to the radiating edge is presented. The ratio of the two frequencies can be well controlled by the aspect ratio of the step-loading dimension. Simulations performed on the designed antennas showed good dual band operation of fi =1.575 GHz (GPS) and A = 1.8 GHz (GSM) with better than -l0dB achieved return losses. Statisfactory performance of dual matching are achieved when coaxial and EMC feeds are employed. The accuracy of the design is validated by using two different electromagnetic simulation softwares.